Salvage Therapy in Cancer Patients With Hepatitis C Infection Failing Direct-Acting Antivirals: A Prospective Study. (4th October 2017) - Pritchard, Haley; Jandhyala, Deeksha; Economides, Minas Platon; Hosry, Jeff; Torres, Harrys
Abstract: Background: Direct-acting antivirals (DAAs) are commonly used in Hepatitis C (HCV)-infected cancer patients. While treatment failure in these patients is rare, little information exists regarding antiviral salvage therapy. We evaluated the treatment outcomes of this patient population. Methods: Cancer patients who received initial DAAs (01/2014-06/2016) were analyzed for viral relapse, defined as reappearance of HCV RNA in serum after discontinuation of DAAs. We evaluated safety and efficacy of salvage. RAS (resistance-associated substitutions) to NS5A/B and NS3 were identified using commercially available assays (population sequencing). Results: Of 160 patients enrolled in a prospective observational study, 15 (15/160; 9%) experienced treatment failure. Of these, 7 received salvage therapy (7/15; 47%) (Table). The majority of patients were men (86%), cirrhotics (57%), and had solid tumors (71%). Ultimately 3/7 (43%) patients achieved  sustained virologic response (SVR). Of the 4 patients who failed first salvage treatment, 3 (75%) had RASs prior to such therapy, 3 (75%) had HCC, and 1 (25%) underwent second salvage. None of the patients experienced grade 3/4 adverse events. Conclusion: HCV relapse after DAAs is rare in cancer patients, but the efficacy of salvage is suboptimal. More effective rescue therapies are needed. Disclosures: All authors: No reported disclosures.